2013
DOI: 10.1037/a0029160
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative contributions of semantic and lexical-phonological information to immediate recognition.

Abstract: Several neuropsychological studies have reported that patients with memory deficits exhibit a dissociation of effects attributed to semantic and lexical-phonological information in verbal working memory (e.g., Reilly, Martin, & Grossman, 2005; Romani & Martin, 1999). The present study reports on 3 experiments conducted with individuals without memory problems to examine the dissociation between the word imageability effect (WIE) and the word frequency effect (WFE). Experiment 1 used a modified semantic recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
(87 reference statements)
0
15
0
1
Order By: Relevance
“…Further studies have qualified this distinction by investigating the nature of the processes underlying WM maintenance as a function of either mechanism. Congruent with prior research on immediate recall from STM (Baddeley, 1966;Baddeley et al, 1975), Camos and colleagues (2011;2013;Mora & Camos, 2013) have shown that rehearsal strongly emphasizes the phonological characteristics of memoranda in complex span tasks.…”
Section: Semantic Representations In Wmmentioning
confidence: 86%
See 2 more Smart Citations
“…Further studies have qualified this distinction by investigating the nature of the processes underlying WM maintenance as a function of either mechanism. Congruent with prior research on immediate recall from STM (Baddeley, 1966;Baddeley et al, 1975), Camos and colleagues (2011;2013;Mora & Camos, 2013) have shown that rehearsal strongly emphasizes the phonological characteristics of memoranda in complex span tasks.…”
Section: Semantic Representations In Wmmentioning
confidence: 86%
“…Further studies with normal participants have also demonstrated similar double dissociations (Nishiyama, 2013(Nishiyama, , 2014. For example, using a dual-task interference paradigm, Nishiyama (2014) showed that disrupting maintenance of words using articulatory suppression or tapping differently affected performance on a homophone (phonological) or synonym (semantic) short-term recognition task.…”
Section: Semantic Representations In Working Memorymentioning
confidence: 94%
See 1 more Smart Citation
“…Words evoke semantic representations based on LTM (e.g., [ 4 ]). Current evidence suggests that such semantic representations can contribute to performance of short-term memory tasks separably from phonological representations (e.g., [ 5 , 6 10 ]). If so, are the semantic representations actively maintained independently from phonological maintenance?…”
Section: Introductionmentioning
confidence: 99%
“…The tangibility criterion is best represented by the concreteness variable defining the distinction between concrete and abstract concepts based on the dual coding and context availability theories. It plays a key role in psycholinguistic research, as well as providing an explanation for many phenomena, such as hemispheric lateralisation in the processing of concrete and abstract concepts (Oliveira, Perea, Ladera, & Gamito, 2013), or ease of retrieval of concrete words compared to abstract ones (Mate, Allen, & Baques, 2012;Nishiyama, 2013).…”
Section: Featural Viewmentioning
confidence: 99%